On some species of Nipponophloeostiba Watanabe, 1962 and Phloeostiba Thomson, 1858 (Coleoptera: Staphylinidae: Omaliinae: Omaliini) - Shavrin, Alexey V. (Zootaxa, 2025)
Taxonomic, diagnostic and faunistic data for three species of Nipponophloeostiba Watanabe, 1962 and two species of Phloeostiba Thomson, 1858 are provided. A new combination is proposed: N. temporalis (Cameron, 1930) comb. nov. (from Phloeostiba). A lectotype is designated for Phloeonomus (Phloeostiba) pinicola Champion, 1920. Three new synonyms are established: N. temporalis = Phloeostiba basui Biswas, 2003 syn. nov., = N. hammondi Shavrin, 2024 syn. nov.; Phloeostiba plana (Paykull, 1792) = Phloeostiba pinicola syn. nov. Phloeostiba plana is redescribed and illustrated; the morphological variability of this species, and several taxa related to Phloeostiba are briefly discussed. The spermatheca of Ph. plana is illustrated for the first time. The aedeagus of Phloeostiba lapponica (Zetterstedt, 1838) is illustrated. Several species are recorded from a certain area for the first time: N. hornabrooki Shavrin, 2024 from Solomon Islands, N. longilobata Shavrin, 2020 from Papua New Guinea, Phloeostiba lapponica from Tuva, Taimyr and Chukotka autonomous regions, and Amur Area (Russia), and Ph. plana from Amur Area (Russia) and Vietnam.